FACTORS AND EFFECTS OF PRIVATE HEALTH SPENDING - O. A. Zarubina; N. N. Sisigina (Фармакоэкономика)
Private health spending in modern developed countries varies considerably depending on the national policy objectives, selected regulatory instruments as well as general socio-economic conditions.The objective of this paper is to analyze key determinants of private health spending.Materials and Methods. To achieve this objective we analyze academic works dealing with theoretical and empirical studies of private health spending.Results. From the analysis the effects of private health spending determining national health financing policy, significant discretionary (breadth and depth of social healthcare system, public health expenditure, regulatory measures on cost sharing, paid medical services, voluntary health insurance) and non-discretionary factors (relative health services price, income and its distribution, age structure, level of education, political preferences) were highlighted.Conclusion. In developed countries priorities of health private spending regulatory policy now are ensuring accessibility of essential health care and preventing consumer’s moral hazard. The most significant discretionary factor influencing the share and amount of private health spending is the management of state guarantees of free medical care; the most significant non-discretionary factor is the income and its distribution.